Dynamics of biochemical indicators in the mesocycle of training in highly qualified weightlifters - Sivokhin I.P.; Mardenova G.B.; Ogienko N.A.; Safargalieva G.N.; Skotnikov V.F. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the dynamics of changes in biochemical parameters in the blood of weightlifters and to identify the magnitude and direction of individual changes in biochemical markers within the mesocycle of the training process before and after participation in international competitions. Methods and structure of the study. Biochemical control was carried out at the final stage of preparation for the Asian Championships against the backdrop of peak training loads and immediately after participation in competitions. Weightlifters (8 women) (n=8), who were members of the national team of the Republic of Kazakhstan, took part in the study. Control was carried out 4 and 2 weeks before participation in the championship and immediately after it. Results and conclusions. During training, weightlifters successfully coped with high training loads with a pronounced focus on activating the creatine phosphate mechanism for energy supply to muscle work. The majority of subjects were characterized by low values of metabolic biomarkers, such as CPK and AST, which indicates a high level of adaptive potential in athletes during the entire training period. Low levels of CPK and muscle tissue damage index had a positive impact on the effectiveness of the training process of weightlifters and made it possible to achieve high rates of growth in sports and technical indicators. As a result, the women’s team performed successfully at the Asian Championships and won 2 gold, 1 silver and 2 bronze medals.